The name of Philippe Thomas = Philippe Thomas' Name - Lebovici, Élisabeth 1953- (Kunsthalle Bern, 2018)
In the artistic activities of Philippe Thomas (1951-1995), there was a determination to disappear: it was his procedure to transfer his title of author onto his collectors. This was the case when selling an artwork, or whenever the author's credit was needed for a commissioned text, and in the institutional co-operations that Thomas was a participant of. With this strategy Thomas worked against his own historicization, erasing his name from the reigning European and North American art fields and with prescience Thomas' put up obstacles to block his future 'googleability' (Hanna Magauer). In recent years, the works and writings of the artist, who also acted on behalf of the semi-fictional agency readymades belong to everyone, again gained greater visibility and as of current are being assigned a place in art history. With this book, Elisabeth Lebovici elaborates on Thomas's strategy to cede and fictionalize authorship and suggests a reading of his work that incorporates questions of gender and reproduction, the multiplicity of the subjects involved, and the unbearable disappearance of Thomas (who died of AIDS-related complications), into the process of enunciation. It is Lebovici's suggestion that the performativity of Thomas's work requires two versions at once: 'the one where one enters into the fiction and the one where one observes the beauty of the arrangement and the plot at work. The one where one is inside and the one where one contemplates it.'
Wendebuch. The book is in two parts, the English and German parts are bound upside down
Keywords: Thomas, Philippe -- 1951-1995; Thomas, Philippe / 1951-1995 / Criticism and interpretation; Thomas, Philippe / 1951-1995; Criticism, interpretation, etc